2017
DOI: 10.1038/s41598-017-01603-9
|View full text |Cite
|
Sign up to set email alerts
|

Protectin DX ameliorates palmitate- or high-fat diet-induced insulin resistance and inflammation through an AMPK-PPARα-dependent pathway in mice

Abstract: Protectin DX (PDX), a double lipoxygenase derivative of docosahexaenoic acid, has been reported to attenuate inflammation and insulin resistance. In the current study, we explored the effects of PDX on hyperlipidemia-induced insulin resistance and inflammation through AMP-activated protein kinase (AMPK) and peroxisome proliferator-activated receptor α (PPARα). PDX attenuated the impairment of insulin receptor substrate 1/Akt–mediated insulin signaling in palmitate-treated differentiated C2C12 cells and soleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 47 publications
(60 reference statements)
7
26
0
Order By: Relevance
“…PDX ameliorates hepatic gluconeogenesis and systemic insulin resistance via inducing IL‐6 release from skeletal muscle, similar to the effects of exercise. In previous studies, PDX has been reported to attenuate insulin resistance in skeletal muscle and adipocytes through an AMPK‐dependent pathway. Additionally, exercise has been reported to improve hepatic insulin resistance through downregulation of serum fetuin‐A .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…PDX ameliorates hepatic gluconeogenesis and systemic insulin resistance via inducing IL‐6 release from skeletal muscle, similar to the effects of exercise. In previous studies, PDX has been reported to attenuate insulin resistance in skeletal muscle and adipocytes through an AMPK‐dependent pathway. Additionally, exercise has been reported to improve hepatic insulin resistance through downregulation of serum fetuin‐A .…”
Section: Discussionmentioning
confidence: 95%
“…As reported by White et al, PDX could ameliorate hyperlipidaemia‐induced inflammation and insulin resistance via skeletal muscle‐secreted IL‐6 signalling, mediating the modulation of hepatic glucose metabolism. Recently, PDX was demonstrated to alleviate inflammation and insulin resistance in mouse skeletal muscle and adipocytes through the AMP‐activated protein kinase (AMPK)‐signalling pathway . To the best of our knowledge, no clear evidence for the direct effects of PDX on insulin resistance in hepatocytes has been found.…”
Section: Introductionmentioning
confidence: 99%
“…LA biosynthesis and metabolism requires some of the same enzymes used for EPA synthesis and metabolism, including the production of downstream metabolites 32,33 . Moreover, LA's consumption in the western diet is [14][15][16][17][18] times the amount required to prevent LA deficiency 22,46 and LA's effects on insulin sensitivity are strongly debated [46][47][48][49][50][51][52][53] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, overexpression of RvE1's receptor ERV1/ChemR23 improves hyperglycemia and hepatic steatosis of male mice 15 . There is also rigorous evidence that DHA-derived SPMs ameliorate insulin resistance 10,13,[16][17][18][19] . The DHA-derived SPM protectin D1 alleviates insulin resistance by controlling skeletal muscle IL-6 secretion and resolvin D1 enhances glucose tolerance by targeting adipose tissue macrophage polarization 13,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that metabolic impairment is important for AF pathophysiology [45]. Notably, PPARα-dependent AMPK activation could result in suppressed inflammation [46]. Therefore, we speculate that reduction of fecal metabolites such as palmitoleic acid in RAF patients might contribute to excessive inflammation and facilitate AF recurrence.…”
Section: Discussionmentioning
confidence: 92%